Vaconyms of the Village Pishchanyi Brid of the Dobrovelychkivskyi District Kirovograd Region (Linguostylistic Studies, 2016)
The article considers the dialectal material presenting a group of onymic vocabulary, defined as vaconyms (the case study of the vaconyms of the village Pishchanyi Brid, Dobrovelychkivskyi district, Kirovograd region). The vaconyms are classified according to the specific motivational peculiarities and tendencies of giving names to animals. The author suggests classification of these tendencies according to the external/appearance features of an animal, its behavior and temper, the period of birth, the owner’s attitude to the animal and other criteria. It has been revealed that in the majority of cases the names to the bulls and cows are given by their owners and other people caring for them. The study identified the onyms that have been changing since the birth and throughout the animal's life. Among the analyzed vaconyms there have been selected those which were created on the basis of human names, surnames, patronymics, nicknames. The author claims that some of the vaconyms indicate even to the nationality of their owners, but those indicating color, temper and nature of animals are the most frequently met. Key words: methods of studying dialects, dialect, dialectal phenomenon, vaconym, dictionary of dialects. References